Identifikasi Ras Wajah dengan Menggunakan Metode Deep Learning Model Keras - Avrijsto Amandri Achyar; Ali Muhammud Olow; Muhammad Rizky Perdana; Andika Sundawijaya; Aaqila Dhiyaanisafa Goenawan (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2022)
Humans have various types which are called races. The human race can be identified by many things, from the shape of the body to the color of the body. Of the many ways to identify the human race, the author also thinks whether a computer can identify the human race based on skin color. Nowadays, computers have developed in such a way that there are many possibilities that computers can also do this.